Delegation and Performance in the Public Sector: A Study of Selected Federal Ministries, Departments and Agencies (MDAS) 2015-2025 - Huoma Mmam Atuzie (JOURNAL OF PUBLIC ADMINISTRATION AND SOCIAL WELFARE RESEARCH, 2026)
This study examined the effect of delegation on performance in selected Federal Ministries, Departments, and Agencies (MDAs) in Rivers State from 2015 to 2025, with a focus on administrative efficiency and employee effectiveness. The study was anchored on Participatory Management Theory, which emphasized employee involvement in decision making through delegation as a means of enhancing performance. A survey research design was adopted, and data were collected from a total population of 375 staff, out of which 350 valid responses were analyzed, representing a response rate of 93.33%. Data were obtained through structured questionnaires and analyzed using descriptive statistics and chi-square inferential techniques at a 0.05 level of significance. The findings revealed that delegation had a significant impact on administrative efficiency, as the calculated chi-square value (493.71) exceeded the critical table value (12.59), leading to the rejection of the null hypothesis. Similarly, delegation had a significant effect on employee effectiveness, with a chi-square value (345.95) greater than the table value (12.59). The study concluded that effective delegation enhances organizational performance by improving efficiency and employee productivity in public sector institutions. The study recommended that public sector managers should adopt structured delegation practices and provide adequate training to improve employees’ capacity and performance.